2017
DOI: 10.1002/slct.201701572
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Exhibits Recalcitrance‐Associated Features Following the Consolidated Bioprocessing of Populus trichocarpa Natural Variants

Abstract: Because cellulosic ethanol production remains cost‐prohibitive„ advances in consolidated bioprocessing (CBP) have been directed towards lifting this restriction. CBP reduces the need for added enzymes and can potentially slash ethanol production costs through process integration. Clostridium thermocellum, a CBP microorganism, organizes its enzymes in a multi‐enzyme complex ‐ a stark contrast to fungal enzymes. Nonetheless, recalcitrance may limit the extent of biomass deconstruction. Herein, six Populus were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…S5A). The CBI reference poplar line (GW-9947) was previously identified as a low recalcitrance poplar natural variant with reduced lignin and a high syringyl-to-guaiacyl (S/G) ratio [ 18 ], a difference confirmed by the py-MBMS lignin analysis results reported here.
Fig.
…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…S5A). The CBI reference poplar line (GW-9947) was previously identified as a low recalcitrance poplar natural variant with reduced lignin and a high syringyl-to-guaiacyl (S/G) ratio [ 18 ], a difference confirmed by the py-MBMS lignin analysis results reported here.
Fig.
…”
Section: Resultssupporting
confidence: 69%
“…4 E). A higher S/G ratio in the residual solids following C. thermocellum CBP fermentation of poplar wood has been previously described [ 16 , 18 20 ]. One hypothesis for explaining this result is that some of the hemicellulose or cellulose solubilized by C. thermocellum is associated with lignin that has a higher G/S ratio, which was preferentially solubilized along with the glycans.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even for the same feedstock variety, however, heterogeneity of the biomass quality is prevalent, and the result is an uncertain final product yield. Several recent studies have shown that multiple physicochemical properties comprehensively affect the biomass recalcitrance and the subsequent sugar release and/or fuel production [ 12 15 ]. Those factors include, but not limit to, cellulose crystallinity and degree of polymerization, lignin content, lignin S/G ratio, and lignin molecular weight.…”
Section: Introductionmentioning
confidence: 99%